Sensory Characteristics and Nutritional Content of Dragon Fruit Peel Cookies with Stevia Substitution - Adelina, Nadya Mara; Giovani, Sarah; Jameelah, Maryam; Hidayanti, Yurike Febrilian; Zahra, Syarifah Fatimah; Rosianajayanti, Rosianajayanti (Diponegoro University, 2025)
Indonesia ranked 5th in the world for the highest number of diabetes sufferers in 2021 and continues to rise. One of the developments in low glycemic index food products that is safe for people with diabetes is dragon fruit peel flour cookies. The use of stevia in these products can further reduce the glycemic index. However, the use of stevia can affect the sensory characteristics of the product. This study aimed to determine the concentration of stevia that can be substituted in making dragon fruit peel cookies with mocaf flour, which potentially have a low glycemic index while still being favored by consumers. The study used five formulations of dragon fruit peel cookies, with stevia substitution of 0% (F0), 25% (F1), 50% (F2), 75% (F3), and 100% (F4). A Check-All-That-Apply (CATA), hedonic and ranking sensory tests were performed to determine consumer acceptance of the product. Nutritional composition was performed by comparing the selected formulation with the commercial product with low glycemic index claim. The data were analyzed using One-Way ANOVA (SPSS) and CATA Analysis tools (XLSTAT). The determination of CATA attributes was conducted through a Focus Group Discussion, and results showed that formula F1 was the closest to the ideal product characteristics, dominated by sweet aroma, and milky taste. The hedonic test results indicated that all parameters were quite different among the tested formulas. The ranking test results showed that sample F0 ranked first, followed by F1. The nutritional comparison showed that the only significant difference was the fiber content, which was seven times higher in the F1 cookies compared to the commercial product. Based on these results, the dragon fruit peel cookies with 25% stevia substitution are favored by the panelists and have the potential for a low glycemic index.